The Afterlife of Dead Metaphors: on Derrida’s Pragmatism - Reynolds, Anthony (Revista de Letras, 2009)
This essay analyzes the role of the “dead metaphor” within deconstruction and neopragmatism in an attempt to elucidate some of the surreptitious affi nities between the two discursive formations that would constitute what Derrida has called a “pragrammatology (to come).” On the basis of a thorough metaphorological rereading of philosophical thought that extends from Vico, Nietzsche, and Heidegger to Blumenberg, Derrida and Rorty, this essay argues that deconstruction continues to generate new contexts of meaning and reference in the form of a pragmatism that has long been integral to its discursive identity. Keywords: Deconstruction. Pragmatism. Neopragmatism. Rhetoric. Metaphor. Metaphorology.